2001
DOI: 10.1083/jcb.153.7.1403
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer Amyloid Precursor Protein (APP) and Fe65, an APP-Binding Protein, Regulate Cell Movement

Abstract: FE65 binds to the Alzheimer amyloid precursor protein (APP), but the function of this interaction has not been identified. Here, we report that APP and FE65 are involved in regulation of cell movement. APP and FE65 colocalize with actin and Mena, an Abl-associated signaling protein thought to regulate actin dynamics, in lamellipodia. APP and FE65 specifically concentrate with β1-integrin in dynamic adhesion sites known as focal complexes, but not in more static adhesion sites known as focal adhesions. Overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
183
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(200 citation statements)
references
References 53 publications
12
183
0
2
Order By: Relevance
“…APP-Fe65 complexes are present in neuronal growth cones (6) and regulate cell motility (7). Considering that Fe65 WW domain interacts with Mena (8) and APP also with mDab1 (9), these findings support the hypothesis that the APP-Fe65 complex is involved in actin-based membrane remodeling, neurite growth and/or synaptic plasticity.…”
supporting
confidence: 74%
“…APP-Fe65 complexes are present in neuronal growth cones (6) and regulate cell motility (7). Considering that Fe65 WW domain interacts with Mena (8) and APP also with mDab1 (9), these findings support the hypothesis that the APP-Fe65 complex is involved in actin-based membrane remodeling, neurite growth and/or synaptic plasticity.…”
supporting
confidence: 74%
“…Mena belongs to a small family of proteins involved in the control of cell movement and morphology and in chemotactic responses (37). It was demonstrated that Fe65 and APP are present in dynamic adhesion complexes present on the surface of the cells and that their overexpression causes the acceleration of cell migration (38). Therefore, it can be speculated that an APP/Fe65/Mena complex is involved in the regulation of cell movement.…”
Section: Fe65 Cytoskeleton Remodeling and Cell Movementmentioning
confidence: 99%
“…Networks-The WW domain of Fe65 has been reported to bind to the PL motif of Mena, a cytosolic protein involved in cytoskeletal reconstruction (14,15). But Mena contains not only the PL but also PP motif.…”
Section: Functional Importance Of Group Ii/iii Ww Domains and The Ppmentioning
confidence: 99%
“…The WW domain of Fe65 binds the proline-rich region of Mena, a mammalian homologue of Drosophila melanogaster Ena, which has been identified in a specific screen for dominant mutations that alleviate the Abl phenotype (13,14). Fe65 and ␤-amyloid precursor protein are involved in the reconstruction of actin cytoskeleton, which suggests the concerted action of these proteins with Mena and/or Abl (9,15). The WW domain of FBP30 has been reported to bind the Pro-Arg (PR) motif (10,16).…”
mentioning
confidence: 99%